BUILDING AN INCLUSIVE ORGANIZATIONAL ECOSYSTEM. Issue 104 (18th February 2022) - White, James D.; White, Krista
Abstract: The lead author, the former chair, CEO, and president of Jamba Juice, discusses how organizations can work on issues of diversity, equity, and inclusion (DEI), to make a significant difference internally and externally. According to the authors, "one business leader can't change the whole world, but you do have the power to build a stronger, more diverse ecosystem for all of your stakeholders: consumers, communities, suppliers, employees and investors. A business ecosystem that espouses the same values you've brought to the rest of your business, eliminating bias and racism and assuring justice and equity for all, will wield a powerful influence." The authors also discuss "establishing an inclusive culture throughout your entire supply chain. You can't build an intentional culture without the support and participation of your vendors, suppliers, producers, subcontractors, and all other participants in your network. Moreover, as you intentionally build an inclusive supply chain by working with companies owned or operated by people of color, women, and members of the LGBTQIA+ community, you help build wealth within underserved populations." Finally, they note that "the hard work of dismantling long held systems of inequality will take time, but will help create the foundation for a new paradigm of equality."